Evaluating Rock Mass Quality and Critical Depth for Rockburst Hazard in Deep Mines - Takhanov, D. K.; Sapinov, G. K.; Balpanova, M. Zh.; Ivadilinova, D. T.; Zharaspayev, M. A.; Abdrasheva, Z. Zh. (Civil Engineering Journal, 2025)
This study investigates the geomechanical behavior of the rock mass at the Zhayssan mine in Kazakhstan, focusing on improving the safety of deep mining operations. The objective is to forecast the working strength of rock masses and assess the associated rockburst risks, especially given the limited existing data on the mechanical properties of the site’s rocks. To achieve this, we conducted comprehensive laboratory tests to determine rock strength characteristics, brittleness, and elastic energy accumulation capacity. We analyzed these data using the Rock Quality Designation (RQD) indicator and constructed a simplified geomechanical model of the deposit. Our findings reveal that rock mass quality improves with depth, as indicated by higher RQD values and reduced fracturing intensity; however, this improvement coincides with an increased risk of dynamic rock pressure events, particularly beyond the analytically estimated critical depth of approximately 400 meters. The study’s novelty lies in its integration of local testing data with comparative regional data, allowing for a more robust preliminary risk assessment despite limited local measurements. As promising directions, the paper suggests further laboratory and field research to refine methods for forecasting the strength and stability of mine workings.